2011
DOI: 10.2136/sssaj2009.0365
|View full text |Cite
|
Sign up to set email alerts
|

Processing Tomato Nitrogen Utilization and Soil Residual Nitrogen as Influenced by Nitrogen and Phosphorus Additions with Drip‐Fertigation

Abstract: Titnely sufficient water supply through drip irrigation or fertigation may increase nutrient demand of processing tomato {Lycopersicon esculentum Mill.) due to increases in yield production. However, excessive nutrient application could result in crop Itixury uptake and enrichment in soil profile, especially mineral N, with the latter potentially causing environmental concerns. A study was conducted to determine the responses of crop N utilization and post-harvest soil profile mineral N to fertilizer N and P a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
3
14
0
2
Order By: Relevance
“…However, plant total N uptake was not affected by fertilizer P input as evidenced by the opposite effects of P on N concentration and biomass. In a recent field study of fertilizer N and P effects on high yielding drip fertigated processing tomato, Zhang et al (2011) reported that fertilizer P rates, ranging from 0 to 87.3 kg P ha -1 , had no effects on plant N uptake, apparent N recovery, or post-harvest soil N. The soil P fertility in the current study ranged from medium to high levels for processing tomato according to provincial guidelines (OMAFRA 2008). The medium to high background soil P fertility might provide sufficient P required for healthy tomato growth, thus having no effects on tomato N uptake and soil N. Although soil N was not affected by fertilizer P input, post-harvest water extractable soil P and Olsen P increased linearly in response to P application (Liu et al 2011a), suggesting high fertilizer P input exacerbated the adverse P effects on surrounding water systems.…”
Section: Water Management Effectsmentioning
confidence: 46%
See 3 more Smart Citations
“…However, plant total N uptake was not affected by fertilizer P input as evidenced by the opposite effects of P on N concentration and biomass. In a recent field study of fertilizer N and P effects on high yielding drip fertigated processing tomato, Zhang et al (2011) reported that fertilizer P rates, ranging from 0 to 87.3 kg P ha -1 , had no effects on plant N uptake, apparent N recovery, or post-harvest soil N. The soil P fertility in the current study ranged from medium to high levels for processing tomato according to provincial guidelines (OMAFRA 2008). The medium to high background soil P fertility might provide sufficient P required for healthy tomato growth, thus having no effects on tomato N uptake and soil N. Although soil N was not affected by fertilizer P input, post-harvest water extractable soil P and Olsen P increased linearly in response to P application (Liu et al 2011a), suggesting high fertilizer P input exacerbated the adverse P effects on surrounding water systems.…”
Section: Water Management Effectsmentioning
confidence: 46%
“…In a previous field study of drip fertigated processing tomato, Zhang et al (2011) found that plant total N uptake averaged 256 kg N ha -1 at an N rate of 240 kg N ha -1 . In the current study, plant total N uptake only averaged 185 kg N ha -1 in the DI treatment and 147 kg N ha -1 in the NI treatment using a higher N fertilizer rate of 270 kg N ha -1 .…”
Section: Water Management Effectsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, plant fertilizer uptake plays a key role in the soil fertilizer cycle. This issue can only be analysed in fertigation experiments extending to the whole crop cycle (Janat, 2008;Zhang et al, 2011) or even to a whole hydrological year. In such experiments, fertilizer use efficiency (ratio of crop yield to total applied fertilizer) is an important indicator.…”
Section: Field Experimentationsmentioning
confidence: 99%